Understanding cultural geography as a pseudo-diffusion process: The case of the Veneto Region - Guido Ferilli; Pier Luigi Sacco; Massimo Buscema; Giorgio Tavano Blessi (Economies, 2015)
In this paper, we study the cultural geography of the Veneto Region on the basis of a pseudo-diffusion approach to the analysis of the inherent semantic spatial data. We find somewhat surprising results, and, in particular, that Venice, indisputably the Region's cultural hub in terms of concentration of activities and facilities, global visibility and attraction of resources, plays a marginal role in determining the momentum of cultural initiative at the regional level as of 2007 data. The areas with the greater momentum are relatively marginal ones but characterized by a strong presence of design-oriented companies that are actively engaging in culture-driven innovation in a context of gradually horizontally-integrated clusters. Our findings call for a revision of the traditional policy approaches that identify centralities in terms of concentration of activities and facilities based on past dynamics, and to design policies accordingly. We argue in favour of a more forward-looking, evidence-based approach.
Keywords: C38; C45; R12; Z10; 330; cultural geography; cultural activities and facilities; culture-led local development; pseudo-diffusion process; topological weighted centroid